In situ investigations into mining-induced hard main roof fracture in longwall mining: A case study. (December 2019) - Yang, Shang; Wang, Jun; Li, Xuehui; Ning, Jianguo; Qiu, Pengqi
Abstract: To better control strata behavior, it is necessary to understand the mining-induced hard main roof movement and fracture in longwall mining. In situ investigations were carried out on the 78, 121 working face at the Jiangjiawan Coal Mine, Datong Coalfield, China. The longwall-mining-induced hard main roof movement and fracture were investigated by using digital panoramic imaging and a single-position extensometer. Then, geometric computational models were developed to estimate some parameters to describe the hard main roof fracture. Field observations indicate that after the mining of the 78, 121 working face, the hard main roof was broken not only near the coalface regions but also near the side of the longwall panel. In accordance with in situ surveys and geometric computational models, the lateral fracture span, strike fracture span and final rotation angle of the broken main roof of the 78, 121 working face were 15.56 m~23.97 m, 16 m~24 m, and 4.02°, respectively. In addition, field measurements found that the periodic roof weighting interval is equal to the strike fracture span and the lateral fracture span. This method provides a possible way to provide advance estimates of the above two parameters. Highlights: The longwall-mining-induced hard main roof movement and fracture is investigated by in situ investigated. A geometric computational model is developed to estimate lateral fracture span and final rotation angle of the broken main roof. The periodic roof weighting interval is equal to the strike fracture span and the lateral fracture span.